Is schizoaffective disorder a distinct categorical diagnosis? A critical review of the literature - Daniel J Abrams (Dove Medical Press, 2008)
Daniel J Abrams1, Donald C Rojas1, David B Arciniegas1,21Department of Psychiatry; 2Neurobehavioral Disorders Program, Departments of Psychiatry and Neurology, University of Colorado School of Medicine, Denver, CO, USAAbstract: Considerable debate surrounds the inclusion of schizoaffective disorder in psychiatric nosology. Schizoaffective disorder may be a variant of schizophrenia in which mood symptoms are unusually prominent but not unusual in type. This condition may instead reflect a severe form of either major depressive or bipolar disorder in which episode-related psychotic symptoms fail to remit completely between mood episodes. Alternatively, schizoaffective disorder may reflect the co-occurrence of two relatively common psychiatric illnesses, schizophrenia and a mood disorder (major depressive or bipolar disorder). Each of these formulations of schizoaffective disorder presents nosological challenges because the signs and symptoms of this condition cross conventional categorical diagnostic boundaries between psychotic disorders and mood disorders. The study, evaluation, and treatment of persons presently diagnosed with schizoaffective may be more usefully informed by a dimensional approach. It is in this context that this article reviews and contrasts the categorical and dimensional approaches to its description, neurobiology, and treatment. Based on this review, an argument for the study and treatment of this condition using a dimensional approach is offered.Keywords: schizoaffective disorder, schizophrenia, bipolar disorder, manic-depressive disorder